Solve the system: `9x + 3y = 2`

`y = -3x + 5/3`

First, multiply 2nd equation by 3 nd rewrite in `ax + by =c` form.

This gives us: `3y = -9x + 5`

`-9x - 3y = -5`

Using the elimination method, add the 2 equations together.

`9x + 3y = 2`

`-9x-3y = -5`

`0 = -3`

Since `0!=-3,`

there is no solution.

**Therefore, choice "c - no solutions" is the correct solution.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now